DOZ047.36: Thoracoscopic esophageal internal axial traction for long- gap esophageal atresia. (24th June 2019) - Juricic, M; Panait, N; Podevin, G; Bonnard, A; Lopez, P; Grossos, C; Fourcade, L; Merrot, T; Boubnova, J; Dariel, A
Abstract: Aim of the Study: Long-gap esophageal atresia (LGEA) remains a surgical challenge. This study aimed to report the results of thoracoscopic esophageal axial internal traction in LGEA. Methods: This multicenter observational study included retrospectively neonates who underwent primary thoracoscopic esophageal axial internal traction for LGEA between June 2017 and July 2018. LGEA was defined as the technical impossibility to perform a primary esophageal anastomosis. The Ethical Review Board of our institution approved the study. Main Results: Eight neonates were included with a median gestational age at birth of 35 weeks [25; 37] and a median birth weight of 2266 g [890; 3800], 6 types I and 2 types II according to Ladd's classification. Initial median gap between 2 esophageal ends was 5 vertebral bodies [4.5; 7]. Internal traction was performed at a median age of 5 weeks of life [1; 17] with a median operative time of 87 minutes. Four patients required at least 2 internal traction procedures. After a mean traction time of 1.5 weeks [1; 13.5], esophageal anastomosis was successfully performed in 7 patients (5 thoracoscopies, 2 thoracotomies) with a median operative time of 165 minutes. One patient needed a colonic interposition. Five of these 7 patients required an esophageal endoscopic dilatation (median number: 4 [2; 6]). Median follow-up was 9.75 months [3; 16]. Conclusions: Thoracoscopic esophageal axial internal traction for LGEA was a safe and feasible procedure that allowed an esophageal anastomosis in 7 of the 8 patients. Improvement of the procedure requires setting a common protocol concerning the timing of the first internal axial traction and the duration of traction before considering esophageal anastomosis.